Pledgeability and bank lending technology - Dieler, Tobias; Zhai, Wei (Journal of Corporate Finance, 2024)
What is the effect of an expansion of eligible collateral on different lending technologies? We show that expanding eligible collateral (i) increases transactional (T) banks’ interest income and decreases relationship (R) banks’ interest income, (ii) increases average loan volume more for T- than for R-banks, (iii) decreases average loan risk and (iv) decreases T-banks’ non-interest income while it increases R-banks’ non-interest income. (v) In sum, T-banks’ profitability increases and R-bank’s profitability remains unaffected. Expanding the set of collateral from immovable to movable assets typically benefits SMEs because it allows them to obtain secured loans instead of unsecured ones. A-priori, it is unclear whether SMEs will continue borrowing from R-banks or switch to T-banks. R-banks benefit from customer relationships and T-banks have the collateral screening technology in place. We show that competition between T- and R-banks gives T-banks a comparative advantage, but R-banks can substitute lost interest income with non-interest income.